2020
DOI: 10.1017/s0022029919000876
|View full text |Cite
|
Sign up to set email alerts
|

Comparative experiments of electrical conductivity from whey protein concentrates conventional film and nanofibril film

Abstract: We compared the electrical conductivity from two different aggregates of whey protein concentrates (WPC) film: conventional amorphous aggregation at natural pH (pH 6.5) and amyloid fibrils at a low pH (pH 2.0) far away from the isoelectric point. The two types of film fabricated by these solutions with different aggregate structures showed large variations in electrical conductivity and other properties. The WPC fibril film (pH 2.0) exhibited higher electrical conductivity than that of the conventional WPC fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…They concluded that aggregates height did not change significantly with temperature and the aggregates presented a relative height distribution of 10 nm [66]. There are numerous reports that confirm the conversion of native whey at similar conditions of this report into fibril aggregation, which is an indicator that the aggregates obtained in the present study may be arranged as fibrils [52,63,66,68].…”
Section: Afm Characterization Of Whey Protein Aggregatessupporting
confidence: 71%
“…They concluded that aggregates height did not change significantly with temperature and the aggregates presented a relative height distribution of 10 nm [66]. There are numerous reports that confirm the conversion of native whey at similar conditions of this report into fibril aggregation, which is an indicator that the aggregates obtained in the present study may be arranged as fibrils [52,63,66,68].…”
Section: Afm Characterization Of Whey Protein Aggregatessupporting
confidence: 71%